Control intellectualization of the induction soldering process for creating permanent joints. Issue 4 (September 2020) - Tynchenko, V S; Milov, A V; Murygin, A V; Kurashkin, S O
Abstract: The article presents the concept of the control intellectualization for the waveguide paths induction soldering process. This is a concept of the intelligent information system designed to support decision-making in control the technological process of creating permanent connections using induction heating in conditions of incomplete or unreliable information. The system should implement methods for assessing the reliability of information on process parameters, methods for estimating the magnitude of measuring tools errors and compensation methods for obtaining unreliable information, as well as methods for predicting the development of the technological process based on the analytical core of the expert system to generate a control action when measuring devices fail. The implementation of this concept will make it possible to recognize interference with measuring instruments and their failure for the further formation of sustainable process control of induction soldering.